18FDG PET in hallucinating and non-hallucinating patients - Kopecek, Miloslav; Spaniel, Filip; Novák, Tomás; Tislerová, Barbora; Belohlávek, Otakar; Horácek, Jirí (Neuro endocrinology letters, 2007)
OBJECTIVE: The aim of the study was to detect whether the abnormal regional brain activity correlates with auditory verbal hallucination-proneness (AVH) in a group of patients with schizophrenia and schizophrenia-related psychoses. METHODS: 15 patients with prominent AVH (score for hallucination intensity--item 3 in the PANSS > or =4) and 15 control patients without AVH (item 3 PANSS score < or =2) underwent 18FDG positron emission tomography at rest. RESULTS: SPM group analysis revealed an increased uptake of 18FDG in the right middle frontal gyrus (BA46) in subjects with high verbal hallucination score compared to non-hallucinating patients (p<0.001, uncorrected). Activation in BA46 positively correlated with the intensity of hallucinations (Spearman r=0.57; p<0.001). CONCLUSIONS: The observed functional recruitment of the right prefrontal cortex in subjects with high hallucination score may reflect impairment in the integration of intended actions and sensory feedback resulting in misattribution of internal events to an external source. This mechanism may form the cognitive basis for AVH.
Keywords: Prefrontal Cortex; Fluorodeoxyglucose F18; Humans; prefrontální mozková kůra; Case-Control Studies; mapování mozku; Hallucinations; kognice; studie případů a kontrol; schizofrenie; Female; dospělí; fluorodeoxyglukosa F18; halucinace; lidé; Schizophrenia; psychotické poruchy; Brain Mapping; Adult; ženské pohlaví; Male; Positron-Emission Tomography; mužské pohlaví; radiofarmaka; Cognition; Psychotic Disorders; pozitronová emisní tomografie; Radiopharmaceuticals